UPAYA PENANAMAN NILAI-NILAI KEJUJURAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP TAKHASSUS AL-QUR’AN WONOSOBO - Nur Farida (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
The problem that prompted the authors to conduct this study is the lack of parental roleat home in instilling the values of honesty in children which impact on the child in school.In addition, the role of teachers in schools in an effort to instill the values of honesty inlearning Islamic education it is still less than the maximum, especially in junior highschool Takhassus Al-Quran Wonosobo. Therefore the role of parents at home and teachersat school learning Islamic education is very important in the context of growing the valueof honesty in children, especially in junior high school Takhassus Al-Quran Wonosobo.This study is a qualitative field research with the descriptive type of approach. Samplingby purposive sampling, ie in accordance with the purpose of research conducted. Samplestaken at random as much as 25% or 68 respondents from the general population eighthgrade junior high school Takhassus Al-Quran Wonosobo, amounting to 273 learners. Themethods used to collect data include: methods of observation, interviews, document studymethods, and, in the questionnaire method. The technique of data analysis is descriptiveanalysis using qualitative techniques. The results based on interviews showed that 70% ofstudents answered yes (positive) and supports the efforts of planting the value of honestyin learning Islamic education in junior high school Takhassus Al-Quran Wonosobo, basedon calculations on any number of items showed that 67 or 98.53% of students statedthat they supported the planting value of honesty in learning Islamic education, andcalculations based on each answer option indicates that as many as 70.15% of studentsexpressed a positive attitude towards planting efforts in the values of honesty in juniorhigh school Takhassus Al-Qur 'an Wonosobo.